Proposed Marketing Strategy for Music Through Digital Streaming Music Recommendation System for Independent Musician (Case Study: Ping Pong Club) (The Indonesian Journal of Business Administration, 2021)
The new face of modern music industry has followed the global trend on digitalizing music consumption through the invention of music streaming apps, or known as the digital streaming platform. While the DSPs are using the preference base algorithm for their consumers to stream the kind of songs they like, indie musicians are mostly benefitted from the algorithm. The challenge for indie musicians is on how to market their music through managing this preference base algorithm in the DSPs. This journal is a result of experimentation held with author’s music project called Ping Pong Club. A set of experimentation is done by using some of their tracks in order to show the boosted streaming numbers between the ‘treated’ songs and the ‘untreated’ one, along with the explained details from which streaming sectors matters. An implementation plan and strategy is applied to show how managing the preference base algorithm works on increasing the digital streaming sales. Keywords: Music Industry, Digital Streaming